2012
DOI: 10.1080/15426432.2012.716287
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Spiritual, and Support Coping, and Psychological Well-Being Among Older Adults in Assisted Living

Abstract: This study explored the role of stress and coping on the psychological well-being of 316 older adults in assisted living. Hierarchical regression revealed that high stress was significantly associated with high depression and low life satisfaction, while high levels of social support and spiritual coping mechanisms were significantly related to low depression and high life satisfaction. The findings indicated the necessity of appropriate assessment and intervention for older adults with stressful events and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 71 publications
(87 reference statements)
2
13
0
Order By: Relevance
“…The mean score 2.28 of respondents was less than the mean score of 3.72 for older adults in assisted living facilities (Lee, Besthorn, Bolin, & Jun, 2012), but was slightly higher than the mean score of 2.1 for older African American women (Pedraza, Dotson, Willis, Graff-Radford, & Lucas, 2009). To assess whether the findings explained small differences in affect among participants with no or few depressive symptoms, post-hoc analyses were conducted in which we re-ran correlations after removing participants who had a score of 5 or higher on depressive symptoms.…”
Section: Discussionmentioning
confidence: 62%
“…The mean score 2.28 of respondents was less than the mean score of 3.72 for older adults in assisted living facilities (Lee, Besthorn, Bolin, & Jun, 2012), but was slightly higher than the mean score of 2.1 for older African American women (Pedraza, Dotson, Willis, Graff-Radford, & Lucas, 2009). To assess whether the findings explained small differences in affect among participants with no or few depressive symptoms, post-hoc analyses were conducted in which we re-ran correlations after removing participants who had a score of 5 or higher on depressive symptoms.…”
Section: Discussionmentioning
confidence: 62%
“…In all, 45 studies reported that they excluded individuals with cognitive impairment or a diagnosis of dementia, of which 30 were cross-sectional studies (58.8%) [11,12,17,19,24,30,31,32,33,37,58,59,60,62,63,64,65,66,69,72,73,75,76,77,78,88,89,90,91,92] and 15 were longitudinal studies (68.2%) [2,3,4,8,10,18,20,21,25,26,34,45,46,48,49]. Cognitive function was equally assessed in clinical studies (n = 11) and in community-based studies (n = 12).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of depression in older medical inpatients and patients in primary health care has been reported to be high in several studies [12,30,45,60,75]. Depression or depressive symptoms are the most common comorbidity in older persons with physical health difficulties [15,141,142].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 depicts the ranges, means, and standard deviations of the main variables, as well as the correlations of depressive symptoms with each of the other variables. The mean score on depressive symptoms was a low 2.28 (SD ¼ 2.77), which is lower than the mean score found among older adults in assisted living facilities (Lee, Besthorn, Bolin, & Jun, 2012), but higher than the mean score reported for a general sample of older African American women (Pedraza, Dotson, Willis, Graff-Radford, & Lucas, 2009). Based on their scores, most respondents (86.5 %) did not have depressive symptoms, whereas 9.3 % had mild depressive symptoms, 1.4 % had moderate depressive symptoms, and 2.3 % had severe depressive symptoms.…”
Section: Discussionmentioning
confidence: 90%